ملامح من البيان النبوي : دراسة تأصيلية = Characteristics of the Prophet’s eloquence: foundational study = Kajian dasar ciri-ciri Kefasihan Nabi - Gasmelsid, Saadeldin Mansour (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, IIUM, 2011)
يركز هذا البحث في بيان أهم كتب البيان النبوي من حيث اللغة والشرع، مع إيضاح ما فيها من اسرار اللغة من البلاغة والبيان البديع، ومن ثم يهتم البحث بذكر معاني البيان وما يدل عليه، وأقسامه، وسرد بعض أساليب البلاغة النبوية، كالصوت الجهير، والحركة والإشارة، والتكرار، والإيجاز، وغيرها، وويتجه البحث إلى بيان بعض نماذج من جوامع الكلم التي أوتيها رسول الله صلى الله عليه وسلم وبيان وجه البلاغة فيها، كسحر البيان ونحوه، ويتطرق كلام الباحث إلى بيان معنى الحديث وبلاغته مع ذكر بعض الأمثلة للأحاديث التي تدل على بلاغته صلى الله عليه وسلم في الحديث والبيان. *********************************************************** This research focuses on explaining the most important works on the eloquence of the Prophet Mohammad (SAW) both in linguistic and legislative ways. Furthermore, it explains the linguistic secrets of these works which contain eloquence and rhetoric. And then the research undertakes the meaning of eloquence and its divisions; it enumerates some of the types of eloquence and rhetoric of the Prophet. For example, voice bass, sign and gesture, repetition, brevity, etc. The research explains some of the examples of the concise speech of the Messenger of Allah (SAW) and explains the rhetorical aspects of it such as the magical expression and the like. The research defines the meaning of the traditions of the Prophet and their eloquence with a few examples of those traditions which demonstrate the eloquence of the Prophet in conversation and speech. ********************************************************* Kajian ini tertumpu pada penjelasan karya Nabi Muhammad (SAW) dalam kefasihan beliau dalam linguistic dan perundangan. Selain itu, kajian ini menjelaskan rahsia linguistik bagi karya-karya ini yang mengandungi kefasihan dan retorika beliau. Kajian ini juga menumpu kepada makna kefasihan dan divisyennya; ia juga menyebut beberapa jenis kefasihan dan retorik Nabi. Sebagai contoh, bes suara, tingkah laku, pengulangan, keringkasan, dan lain-lain. Kajian ini menjelaskan bebrapa contoh hujah ringkas Nabi dan aspek retoriknya. Kajian ini mendefinisikan tradisi Nabi dan kefashiannya dengan bebrapa contoh tradisi yang memaparkan kefasihan dalam perbualan dan pertuturan beliau.